2022
DOI: 10.1016/j.wem.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Kids With Altitude: Acute Mountain Sickness and Changes in Body Mass and Total Body Water in Children Travelling to 3800 m

Abstract: Introduction-We explored the incidence of acute mountain sickness (AMS) and extravascular lung water (ELW) in children in relation to changes in body composition and peripheral blood oxygenation (S p O 2 ) during 1 week of acclimatization to 3800 m.Methods-In a prospective cohort study, 10 children (7 female, ages 7-14 y) and 10 sex-matched adults (ages 23-44 y) traveled via automobile from sea level to 3000 m for 2 nights, followed by 4 nights at 3800 m. Each morning, body mass and body water (bioelectrical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…While we tended to observe larger increases in QICA than QVA in both groups, the relative contribution of the ICA to gCBF was consistent between groups and across time at BL, CC and B1. We have previously reported that the incidence of acute mountain sickness is greater in children compared to adults upon ascent to 3800 m (Rieger et al, 2022); however, the current findings indicate that these age-related differences are unlikely to be related to differences in cerebrovascular reactivity to high altitude.…”
Section: Cerebrovascularcontrasting
confidence: 87%
See 1 more Smart Citation
“…While we tended to observe larger increases in QICA than QVA in both groups, the relative contribution of the ICA to gCBF was consistent between groups and across time at BL, CC and B1. We have previously reported that the incidence of acute mountain sickness is greater in children compared to adults upon ascent to 3800 m (Rieger et al, 2022); however, the current findings indicate that these age-related differences are unlikely to be related to differences in cerebrovascular reactivity to high altitude.…”
Section: Cerebrovascularcontrasting
confidence: 87%
“…In contrast, in adults SV was only significantly reduced from BL by the fourth day at 3800 m. Most investigations of cardiac function at high altitude in adults implicate a maintenance, then gradual reduction of SV (Alexander & Grover, 1983; Klausen, 1966; Stembridge et al., 2014); however, when data from a prior study of children are extrapolated (Allemann et al., 2012), an approximate 20% reduction in SV was apparent after only 40 h at 3450 m, similar to our findings. A more immediate reduction in SV in children could be attributable to more rapid loss of body water (Rieger et al., 2022) and subsequently plasma volume in children; however, there is also evidence to suggest that the balance between sympathetic and vagal control of cardiac output may differ between children and adults (Galanter et al., 1999; Harteveld et al., 2021). In support of this, we found that MAP was increased at high altitude in children, but not in adults, and furthermore, during exercise at 3540 m, adults have previously demonstrated a 16% reduction in maximal HR, while no reduction in maximum HR in children aged 9–12 was observed (Kriemler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that these differences were observed following nocturnal hypoxic residence and not upon acute hypoxic exposure, as employed in some previous work [ 17 , 18 ]. Additionally, recent work on subacute hypoxic exposures by Rieger and colleagues [ 19 , 20 ] demonstrated a higher incidence and severity of Acute Mountain Sickness but also showed comparable ventilatory responses and cerebrovascular responses in children as compared to adults.…”
Section: Introductionmentioning
confidence: 99%